The Use of Context-Clue and Read Aloud Instruction to Enhance Junior High School Students’ Vocabulary Ability Through Literature (Comparative Study at SMPN 1 Cisarua, Bandung Barat) - Caroline V Katemba, Nelson Balisar Panjaitan, Rindu Bintang, (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2017)
The aim of this research is to find out the better method between context-clue and read aloud instruction to enhance students’ vocabulary. This research is quantitative research with comparative design. The research was conducted in SMPN 1 Cisarua, Bandung Barat. Population on this research was 8 grader of Junior High School and the sample was 8A grader that contain 30 students and 8B grader contain 32 students. 8A was given Context-Clue Instruction treatment and 8B was given Read Aloud Instruction Treatment. Statistic test that researcher used was Mann-Whitney Test. The result of this research showed there is no significant difference in enhancing vocabulary ability between students who are taught through context-clue instruction and students who are taught through read aloud instruction. Keywords: Vocabulary ability, Context-Clue Instruction, Read Aloud Instruction